Elastic stable intramedullary nailing alone for unicameral bone cysts of the humerus in children: a mid-term follow-up study - Liu, Shoushen; Li, Fujiang; Wang, Yanzhou; Zhang, Mingang; Li, Tianyou (Frontiers in Pediatrics, 2026)
IntroductionUnicameral bone cyst (UBC) is a common disease in children. There are several different treatment modalities for this condition. Elastic stable intramedullary nail (ESIN) insertion alone was a minimally invasive method that allows for cyst drainage and fracture prevention; however, the treatment outcome remains unclear and inadequately classified. We aimed to evaluate the outcomes of pediatric humeral UBC treated only with ESIN insertion.MethodsThis was a retrospective case series study. Data records included patient demographics, fracture classification, cyst size, treatment strategy, and complications. The Capanna classification was used to determine the outcomes. The potential influential factors for complete healing were analyzed.ResultsA total of 22 patients with an average age at surgery of 7.2 years were included. The average follow-up was 5.0 years (range 2.1–12 years). There were 3 (13.64%) type I, 8 (36.36%) type II, 3 (13.64%) type III, 8 (36.36%) type IV. 2163;. The complete healing rate (type I) and effective rate (type I, II) were 13.64% and 50%, respectively. No factors significantly influenced complete healing. At the last follow-up visit, none of the patients experienced pain or refracture, and their shoulder motion was unlimited.ConclusionIn our study, the use of ESIN insertion alone to treat humeral UBC, on the basis of the Capanna classification, resulted in a complete healing rate of 13.64% and an overall effective rate of 50%.